2016
DOI: 10.1590/0103-8478cr20150342
|View full text |Cite
|
Sign up to set email alerts
|

Onion yield under agroecological farming system using distinct irrigation depths and soil covers

Abstract: The present study was carried out in order to evaluate the effects of irrigation depths applied through drip and presence/ absence of soil cover in onion yield (ETc): 0, 22, 45, 75 and 100% (0, 155, 220.6, 320.5 and 372,7mm in +S condition and 0, 145.5, 207.6, 285, 351, (ETc): 0, 22, 45, 75 e 100% (0; 155; 220,6; 320,5 e 372,7mm na condição SC e 0; 145,5; 207,6; 285

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…Igbadun and Oiganji (2012), Ramalan, Nega, and Oyebode (2010) and Ribeiro et al (2016) observed that irrigation depths had similar effects on the yield of onion bulbs. The reduction in irrigation depth of 36% (321 to 204 mm) in 2014 and of 37% (444 to 278 mm) in 2015 resulted in losses of 29, 30, 33, and 11% and 38, 38, 34, and 17% in TY, MBFW, MBDW and MBD, respectively, in each year.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Igbadun and Oiganji (2012), Ramalan, Nega, and Oyebode (2010) and Ribeiro et al (2016) observed that irrigation depths had similar effects on the yield of onion bulbs. The reduction in irrigation depth of 36% (321 to 204 mm) in 2014 and of 37% (444 to 278 mm) in 2015 resulted in losses of 29, 30, 33, and 11% and 38, 38, 34, and 17% in TY, MBFW, MBDW and MBD, respectively, in each year.…”
Section: Resultsmentioning
confidence: 84%
“…In 2015, irrigation had an opposite effect, as a larger percentage of bulbs had diameters greater than 60 mm. The highest number of bulbs was included in this classification, as found by Ricci et al (2014) and Ribeiro et al (2016). The increase in water deficit favored an increase in the percentage of bulbs with diameters between 30 and 40 mm (smaller class) and with diameter smaller than 30 mm (without commercial value) ( Figure 5).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…O cultivo orgânico de hortaliças com o uso de cobertura morta sobre a superfície do terreno vem sendo empregado e tem proporcionado aumento de produtividade sem impactar os custos de produção (CARVALHO et al, 2018). Além de disponibilizar nutrientes às plantas, minimizando o uso de fertilizantes minerais (EGODAWATTA; SANGAKKARA; STAMP, 2012), o cultivo sobre palhada reduz a perda de água por evaporação, proporcionando aumento na eficiência do uso da água (RIBEIRO et al, 2016). Essa técnica vem sendo adotada por agricultores no cultivo do repolho, porém há poucas informações sobre a necessidade hídrica da cultura nessas condições (KADYAMPAKENI, 2013).…”
Section: Introductionunclassified